The rural tax: comprehensive out-of-pocket costs associated with patient travel in British Columbia - Jude Kornelsen; Asif Raza Khowaja; Gal Av-Gay; Eva Sullivan; Anshu Parajulee; Marjorie Dunnebacke; Dorothy Egan; Mickey Balas; Peggy Williamson (BMC Health Services Research, 2021)
Abstract Background A significant concern for rural patients is the cost of travel outside of their community for specialist and diagnostic care. Often, these costs are transferred to patients and their families, who also experience stress associated with traveling for care. We sought to examine the rural patient experience by (1) estimating and categorizing the various out of pocket costs associated with traveling for healthcare and (2) describing and measuring patient stress and other experiences associated with traveling to seek care, specifically in relation to household income. Methods We have designed and administered an online, retrospective, cross-sectional survey seeking to estimate the out-of-pocket (OOP) costs and personal experiences of rural patients associated with traveling to access health care in British Columbia. Respondents were surveyed across five categories: Distance Traveled and Transportation Costs, Accommodation Costs, Co-Traveler Costs, Lost Wages, and Patient Stress. Bivariate relationships between respondent household income and other numerical findings were investigated using one-way ANOVA. Results On average, costs for respondents were $856 and $674 for transport and accommodation, respectively. Strong relationships were found to exist between the distance traveled and total transport costs, as well as between a patient’s stress and their household income. Patient perspectives obtained from this survey expressed several related issues, including the physical and psychosocial impacts of travel as well as delayed or diminished care seeking. Conclusions These key findings highlight the existing inequities between rural and urban patient access to health care and how these inequities are exacerbated by a patient’s overall travel-distance and financial status. This study can directly inform policy related efforts towards mitigating the rural-urban gap in access to health care.